Analisis kekuatan struktur ramp door haluan pada kapal Ferry Ro-Ro 1500 GT dengan variasi beban menggunakan Finite Element Method - Alamsyah Alamsyah; Amalia Ika Wulandari; Muhammad Uswah Pawara; Muhammad Yusuf Al-Hafidz (Universitas Muhammadiyah Metro, 2022)
Ramp Door is a door to put a vehicle into a Ro-Ro ship or any other type of ship that transports vehicles. The use of Ramp Door is needed to facilitate the process of unloading and loading vehicles from the crossing dock to the ship and vice versa. This study aims to analyze the strength of Ramp Door structure with load variations from various types of vehicles in order to compress the maximum stress results and safety factors. The method used is the FEM method with the help of an element-based application up to. The results of the study obtained the maximum stress value of Ramp Door Bow with MPV vehicle type at an even load is 43.26 MPa. In this type of SUV vehicle, the maximum stress with an even load is 50.37 MPa. In sedan vehicle type the maximum stress with an even load is 37.61 MPa. in commerial vehicle type the maximum stress with an even load is 45.70 MPa. In this type of small truck vehicle, the maximum stress with an even load is 81.53 MPa. In large truck vehicles the maximum stress with an even load is 302.48 MPa. In this type of vehicle, the maximum stress bus with an even load is 178.08 MPa. For the largest safety factor value is a type of Commercial vehicle with a value of 8.91. While the smallest safety factor value is the type of Big Truck vehicle with a safety factor value of 1.01.